Metabolomics-driven comparison of the nutritional and functional food characteristics of postbiotic and probiotic okara - Tay, Clarisse Siew Cheng (2023)
Okara, a nutritious processing side-stream of soybean, poses a significant food waste challenge in regions with high soybean consumption such as Asia. Consequently, its valorization through probiotic fermentation has received considerable attention, but the use of live probiotics in foods raises concerns due to potential side effects and probiotic viability decline over product shelf-life, especially when subjected to cold chain interruptions. To address this, a dual fermentation-heat treatment method with Lactobacillus sp. and Bifidobacteria sp. was employed to produce postbiotic okara. Nutritional and compositional analyses revealed increased soluble fiber by 156%, total isoflavones by 151%, and total phenolic content by 21% when compared to the unfermented control, which was further validated by metabolomic analyzes of okara samples, demonstrating the retention of or enhanced functionality post-heat treatment. Additionally, postbiotic okara extracts exhibited improved inhibitory activity against enzymes α-amylase (IC50 = 13.50 ± 0.56) and α-glucosidase (IC50 = 19.76 ± 0.96) in vitro, as compared to unfermented okara. Overall, the novel processing method was able to increase nutrient retention and functional properties and improve safety of postbiotic okara through the inactivation of live microbes, increasing its versatility as a functional probiotic alternative ingredient suitable for a wider range of consumers.